Shedding of Marburg Virus in Naturally Infected Egyptian Rousette Bats, South Africa, 2017 - Pawęska, Janusz T.; Storm, Nadia; Markotter, Wanda; Di Paola, Nicholas; Wiley, Michael R.; Palacios, Gustavo; Jansen van Vuren, Petrus (Emerging infectious diseases, 2020)
We detected Marburg virus RNA in rectal swab samples from Egyptian rousette bats in South Africa in 2017. This finding signifies that fecal contamination of natural bat habitats is a potential source of infection for humans. Identified genetic sequences are closely related to Ravn virus, implying wider distribution of Marburg virus in Africa.